Cultural Content Analysis of English Textbook “Bahasa Inggris 2” for Senior High School Grade XI - Iranta Purba, Agnes Dwi; Azkiya, Siti Nurul; Qadri, Asri Nurul; An’asy, Zaharil (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
AbstractThis research aims to discover what and how culture is represented in the